Balanced Subsoil and Forest Management in the Context of Challenges and Threats - Loginov, Vladimir Grigoryevich; Ignateva, Margarita Nikolaevna; Yurak, Vera Vasilievna (Economy of Regions, 2020)
The balanced nature management implies full coordination of the economic, environmental and social subsystems, and an appropriate institutional support. The unstable economic situation, increasing environmental problems, deteriorating international relations result in emerging challenges and threats that negatively affect the balanced nature management. For maintaining the balance, it is necessary to identify possible challenges and threats, assess their danger, and implement a set of measures to prevent or reduce their influence. Thus, in this research we identified the challenges and threats endangering the balanced subsoil and forest management. Furthermore, we developed methodological tools for assessing the degree of their danger. We applied a variety of research methods: grouping method, comparative analysis, expert assessments, analogy method. For assessing the threats, we proposed a method that includes calculation of individual and group indicators, as well as of an integrated indicator. We defined threshold values for the integrated indicator to grade the degree of danger. The weighting factors defined by expertise for both individual and group indicators, show the significance of the assessed factors for the end result. We determined how specific economic, social, institutional and environmental threats and challenges influence the mining and forest management. We proposed an assessment algorithm and described 11 systematic steps. Based on the list of initial indicators for each group of threats, we developed a mechanism for calculating aggregate individual indicators. The calculated values of the individual, group, and integrated indicators are demonstrated in the final table. This table allowed comparing the impact of threats on subsoil and forest management and detecting the ones that require urgent preventive measures. The proposed methodological assessment approach can be used for identifying the most dangerous threats and preventing or reducing the consequences of their possible negative effects.